Effect of Atorvastatin on 7,12-Dimethylbenz (α) Anthracene and Testosterone-induced Prostatic Intraepithelial Neoplasia in the Prostate of Wistar Rats: Role of TRPM7 - JianhengChen, JianhengChen; ZhengchaoShen, ZhengchaoShen; PengGu, PengGu; XiaodongLiu, XiaodongLiu; JihongShen, JihongShen; BhavinVyas, BhavinVyas; KunbinKe, KunbinKe (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim/Background: The current study was conducted to examine the influence of atorvastatin in experimentally induced prostatic intraepithelial neoplasia in rats. TRPM7 is a potential therapeutic target for treatment of prostate cancer. Materials and Methods: In this study, we investigated the effects of atorvastatin (25 and 50 mg/kg/BW p.o.) on cell proliferation of prostate induced by a sequential regimen of testosterone plus single administration of 7,12-Dimethylbenz(a) anthracene. Results: Results of present study revealed that the different pattern of prostatic intraepithelial neoplasia with associated High grade PIN in model control group while concurrent treatment with atorvastatin increases the effect by developing a pattern of high grade PIN with dysplasia. Furthermore, atorvastatin treatment produced elevated levels of TRPM7 protein expression with higher Ca/Mg ratio and low ratio of serum testosterone to dihydrotestosterone. Conclusion: The results of the present study indicate that atorvastatin has a promotive role in DMBAtestosterone- induced intraepithelial neoplasia in rats through increasing expression of the TRPM7 channel.
Keywords: Atorvastatin; Testosterone; PIN; Ca2+/Mg2+ ratio; TRPM7